Immersive Technology Strategies. (December 2013) - Wortley, David
This newsletter touches on several recent developments, opportunities, and events in gaming, simulations, gamification, and serious games. For example, World Innovation Summit on Education, OPENChina EU ICT Collaboration, Horizon 2020 Conference, Great Ormond Street Hospital Learning Innovations Conference, Oman Competitiveness Forum, The Gamification Lens Concept, Junior Achievement Leaders Jamboree, The SimRed Gamification Project, Secrets of Gamification Workshop, and finally upcoming conferences and seminars.